On the NICS limitations to predict local and global current pathways in polycyclic systems. (23rd April 2021) - Inostroza, Diego; García, Victor; Yañez, Osvaldo; Torres-Vega, Juan J.; Vásquez-Espinal, Alejandro; Pino-Rios, Ricardo; Báez-Grez, Rodrigo; Tiznado, William
Abstract : Here, we analyze the possibility of predicting local and global current densities in a series of bicyclic hydrocarbons with 4n and 4n + 2 π-electrons from the nucleus-independent chemical shifts (NICS) computations. Abstract : Here, we analyze the possibility of predicting local and global current densities in a series of bicyclic hydrocarbons with 4n and 4n + 2 π-electrons from the nucleus-independent chemical shifts (NICS) computations. Our results show that although it is possible to establish the net current flows through C–C bonds, it is impossible to predict all the local and global weak current density flows. Thus, for polycyclic systems, it is essential to analyze magnetically induced current densities in conjunction with NICS measurements, or with induced magnetic fields, to have an adequate representation of the molecules' magnetic behavior and their relationship with the aromaticity phenomenon.